PEMETAAN PENELITIAN RASIO RETURN ON INVESTMENT (ROI) PADA PERBANKAN SYARIAH DAN KONVENSIONAL: STUDI BIBLIOMETRIK VOSVIEWER DAN LITERATURE REVIEW - Eka Wahyu Hestya Budianto; Nindi Dwi Tetria Dewi (Universitas Trunojoyo Madura, 2023)
This study aims to determine the research mapping regarding the Return On Investment (ROI) ratio in Islamic and Conventional Banking using a mix-method approach, namely the VOSviewer bibliometric study and literature review. Data analysis techniques include: (1) mapping the distribution of journal publications around the ROI ratio; (2) mapping the results of the VOSviewer bibliometric visualization around the ROI ratio based on the number of clusters and their items; and (3) mapping research topics around the ROI ratio using a literature review study. The results showed that: (1) based on the distribution of journal publications, there were 274 journal publications regarding the ROI ratio; (2) based on the mapping of the VOSviewer bibliometric study, the network visualization results around the ROI ratio are divided into 4 clusters and 85 topic items; (3) based on the mapping of literature review studies, there are 28 topics around the influence of the ROI ratio and 38 topics about the determinants of the ROI ratio. The implications and contributions of this research are to map research topics around ROI ratios in Islamic and Conventional Banking which are often or rarely researched by researchers so that they can be a reference for subsequent researchers.